Analysis and modeling of ASIC area at early-stage design for standard cell library selection - Lim, Yang Wei; Hashim, Shaiful Jahari; Kamsani, Noor 'Ain; Mohd Sidek, Roslina; Rokhani, Fakhrul Zaman (IEEE, 2019)
Area-delay curve is an effective technique to compare and select the appropriate library at different target delay constraint. However, generating area-delay curve requires time-consuming synthesis processes. This paper presents a fast area estimation model to allow the designer to select the optimal library for designing area-optimized circuit. The model predicts the area-delay curves for a target circuit based on reduced number of synthesis performed at different frequencies. As compared to the general linear search method, the proposed model with 5 synthesis points results 16.5X-18.6X runtime reduction with average error of 2.74%~5.74% in different height libraries implementation. This shows that the proposed model is beneficial for area optimal library selection at the early stage of design.